Driving High and Low: Heavy Vehicle Drivers and Their Supervisors Facing Digitalization - Alasoini, Tuomo; Ala-Laurinaho, Arja; Känsälä, Marja (Nordic Journal of Working Life Studies, 2022)
Our qualitative study in two Finnish companies examines the view presented as part of the ‘employment crisis’ debate that digitalization is leading to a significant substitution of the work of drivers of heavy road vehicles. The main effects of digitalization thus far on the drivers’ work have been automation of individual vehicle functions, speeding up the communication among them and between them and their supervisors, and more intensive control of work performance. The study does not find support for the claim about labor substitution in the foreseeable future, but, instead, indications of a widening digital divide between drivers and supervisors, leaving drivers as bystanders in learning processes associated with digitalization. Although the results cannot be generalized without reservation to different types of companies or business and labor market environments, the findings of the trends in the drivers’ work and labor market position probably have broader relevance.